Balance and perspectives of the victimization studies in Colombia: hidden and complained real crime. - Quintero Ángel, David (Sociedad y Economía, 2010)
This paper is a review of major studies on the theme of victimization thathave been conducted in Colombia since 1985. Also, an analysis of the realcrime, hidden and complained to the city of Cali, from victimization survey DANE 2003. This is to show that not all sectors of society are affected bycrime in the same way: the lower strata are the most victimized and the mostvulnerable, while the high seems to live in a much better position, in manycases because of private protection. Finally, some methodological findingscontribute to future studies.